Fat boys : a slim book - Gilman, Sander L. (University of Nebraska Press, 2004)
"He is the epitome of health - or a walking time bomb. He is oversexed - or sexless. He is jolly - or hiding the tears of a clown. He is the picture of wealth and plenty - or the bloated, malnourished emblem of poverty. He is the fat man - a cultural icon, social enigma, a pressing medical issue - and he is the subject of this book." "The figures that Sander L. Gilman considers, from the ugly fat man with the beautiful sylph trapped inside to the smart fat boy to the aging body desirous of rejuvenation, appear and reappear in different guises throughout Western culture. And as is often true of marginal cases, they serve to define the shifting center of our dreams and beliefs. A tentative exploration in the world of male body fantasies, Gilman's book asks how the representation of the fat man alters with time and alters how men relate to their own bodies and the bodies of others, both men and women. His examples - ranging from Santa Claus to Sancho Panza, from Falstaff to Babe Ruth, from Nero Wolfe to Al Roker - illustrate the complexity perennially associated with fat men. From discourses about normality to the playing fields of baseball, from Greek male beauty to the fat detective, Gilman's book examines and illuminates how cultures have imagined and portrayed the fat boy."--Jacket